(untitled) (Ingenio Magno, 2020)
The meaning of energy transition is required as a long-term structural change in energy systems. The generation or production of electricity worldwide is presenting a change or transition due to environmental pollution, thermoelectric plants use fossil fuels (coal, natural gas, oil) as a source of heat energy to send water vapor to the turbines that they are connected to electric generators; These fuels, through the emitted gases, increase the temperature on the earth’s surface due to the greenhouse effect, thus causing climate change. This is the global energy scenario: the bet is to reduce Greenhouse Gas (GHG) emissions, for this, it is necessary to change energy sources and consumer technologies. There is increasing awareness about the crisis that is being experienced and the need to make a drastic change in a relatively short time. Corredor, G. (2018). Developed countries are making the energy transition from conventional energy to renewable energy, creating photovoltaic plants, parks offshore and offshore wind, geothermal power plants, among others. Colombia has great potential for renewable energy, there are winds at appropriate speeds to generate wind power in the department of Guajira and the entire Pacific and Atlantic coast, and solar radiation throughout the country is high, very convenient for generation photovoltaic solar and thermal solar. With the tax incentives of Law 1715 of 2014, the interest of agents and investors in non-conventional renewable energy sources (FERNC) has increased. The Energy Mining Planning Unit (UPME) reports, as of May 2018, 303 applications approved to access the benefits of the Law. Benavides et, al. (2018). The interest of various commercial, entrepreneurial, academic, institutional actors and the support received especially from multilateral entities such as the IDB, the GEF, the United States Agency for International Development –USAID–, the World Bank –BM–, the Program of The United Nations Development Program (UNDP), and other agencies interested in promoting the deployment of these technologies in Latin America and especially in Colombia, allow an accelerated growth of the FNCER in the coming years. IDB (2015) The incorporation of power generation projects with FERNC is the way to replace the use of fossil fuels, generate clean energy, mitigate greenhouse gas (GHG) emissions and protect the environment. Non-Interconnected Zones (ZNI) with the support of the Energy Solutions Planning and Promotion Institute (IPSE) are replacing the use of diesel, gasoline and kerosene; fuels that they use for lighting with an electric plant, pumping water for irrigation and consumption, by isolated photovoltaic solar plants and small wind turbines, solutions that generate a social, economic and environmental impact. The SFV produces very low environmental impact as it is considered renewable and clean energy, and when installed near rural housing does not require logging of forests and vegetation as if it happens with the rural networks of the interconnected system. Ramirez et al. (2017) The Energy Mining Planning Unit (UPME) projected in 2012 that the demand for energy in the country would increase between 67% and 105% from that date until 2030, this means a growth between 3% and 4% annually (Aponte & Andrade, 2013). Enough figures to project a renewable energy matrix, an alternative opportunity for business creation and job creation. There are many advantages of renewable energy, they do not pollute, do not generate waste, do not generate any risk to health or the environment.